192k views
2 votes

{ {4e}^(f(x)) }^( - 1) = x - 2
help. how to find f(x) inverse

1 Answer

2 votes

Given function is,

4e^{f(x)^(-1)} =x-2
We need to find
f(x)^(-1). So, we need to isolate
f(x)^(-1) .
Hence, the first step is to remove 4 from the left side. So, multiply each sides by 4. Therefore,

\frac{4e^{f(x)^(-1)}}{4} =(x-2)/(4)

e^{f(x)^(-1)} = (x-2)/(4)
Next step is to take natural log ln to each sides of the equation to get rid of f(x)^-1 from the exponent. So,

n e^{f(x)^(-1)} = ln (x-2)/(4) Since
ln e^x = x

{f(x)^(-1)} = ln (x-2)/(4)
So,
{f(x)^(-1)} = ln (x-2)/(4)

User Matiu
by
6.2k points